2023
DOI: 10.3390/pharmaceutics15031010
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Cellulase from Trichoderma reesei as an Adjuvant for Enterococcus faecalis Biofilm Disruption in Combination with Antibiotics as an Alternative Treatment in Secondary Endodontic Infection

Abstract: Apical periodontitis is an inflammation leading to the injury and destruction of periradicular tissues. It is a sequence of events that starts from root canal infection, endodontic treatment, caries, or other dental interventions. Enterococcus faecalis is a ubiquitous oral pathogen that is challenging to eradicate because of biofilm formation during tooth infection. This study evaluated a hydrolase (CEL) from the fungus Trichoderma reesei combined with amoxicillin/clavulanic acid as a treatment against a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies reported an acidic microenvironment containing peptides and heme-derivatives facilitates the selective expansion of periodontitis-promoting microorganisms, mainly P. gingivalis [ 43 , 44 ]. nMS-nAg-Chx would destroy the beneficial conditions for periodontitis-promoting bacterial growth for the preferential release in an acid microenvironment [ 31 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported an acidic microenvironment containing peptides and heme-derivatives facilitates the selective expansion of periodontitis-promoting microorganisms, mainly P. gingivalis [ 43 , 44 ]. nMS-nAg-Chx would destroy the beneficial conditions for periodontitis-promoting bacterial growth for the preferential release in an acid microenvironment [ 31 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional examples are provided for various biofilms, including B. cereus biofilm 141 , mono-and dual-species biofilms of P. aeruginosa 142 , S. aureus biofilms in a wound model 143,144 , Salmonella variants 145,146 , and Enterococcus faecalis 147 .…”
Section: Biofilm Characterizationmentioning
confidence: 99%
“…From all the cited works, it is evident that a high concentration (ranging from 1 to 30 mg/mL) of various cocktails of fungal cellulases from different strains, such as T. virididae (marketed as Cellulase R-10) 108,135,139,140,146 , T. reesei (marketed as Celluclast) 137,[147][148][149] , and A. niger [142][143][144] , has been used for biofilm eradication. These mixtures are primarily formulated for the hydrolysis of plant cellulose and typically consist of cellobiohydrolases, endoglucanases, and glucosidases in varying proportions.…”
Section: Biofilm Characterizationmentioning
confidence: 99%